2007
DOI: 10.1017/s0266467406003750
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting nitrogen and phosphorus resorption efficiencies in trees and lianas from a tropical montane rain forest in Xishuangbanna, south-west China

Abstract: Tropical montane rain forest is widely considered to be a highly threatened hotspot of global diversity (Brummitt & Nic Lughadha 2003), and one of the least understood humid tropical forest ecosystems in terms of nutrient cycling (Bruijnzeel & Proctor 1995). There is, therefore, an urgent need to improve our understanding of nutrient cycling processes in this ecosystem, including the absorption of nutrients (mainly N and P) from senescing leaves, which may be a key component of adaptive mechanisms that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 22 publications
6
36
0
1
Order By: Relevance
“…NRE had a significant positive correlation with PRE. This correlation suggested that N resorption may be controlled by biochemical processes similar to those that control P resorption, in accordance with the results of studies of wood species in tropical forests [41,42] and wetland graminoids [43]. However, other studies have found no significant correlations between the N and P resorption efficiencies of certain plants [40].…”
Section: Discussionsupporting
confidence: 85%
“…NRE had a significant positive correlation with PRE. This correlation suggested that N resorption may be controlled by biochemical processes similar to those that control P resorption, in accordance with the results of studies of wood species in tropical forests [41,42] and wetland graminoids [43]. However, other studies have found no significant correlations between the N and P resorption efficiencies of certain plants [40].…”
Section: Discussionsupporting
confidence: 85%
“…Resorption data are often presented as NuR efficiency, defined as the proportional withdrawal of a nutrient during senescence (Cartaxana and Catarino 2002, van Heerwaarden et al 2003a, Wright and Westoby 2003, Cai and Bongers 2007, Yuan and Chen 2009a:…”
Section: Resorption Calculation and Data Analysismentioning
confidence: 99%
“…While some studies did not find any relationship (Chapin and Moilanen 1991, Reich et al 1992, Aerts 1996, Lambers et al 1998, Aerts and Chapin 2000, Kazakou et al 2007, Yuan and Chen 2009a, other studies have found resorption efficiency to be related to plant nutrient status (Lal et al 2001, Diehl et al 2003, Wright and Westoby 2003, Kobe et al 2005, Cai and Bongers 2007. When nutrient conservation strategies have been related to plant functional type (Aerts 1996, Diehl et al 2003, Yuan and Chen 2009a, observed differences across growth forms and functional groups have also typically been small.…”
Section: Introductionmentioning
confidence: 97%
“…The degree to which nutrients are resorbed from senescing material determines the quality of litter, which further impacts decomposition rates and the overall sediment nutrient cycling (Aerts andChapin 2000, Cai andBongers 2007). Given this, long term changes in plant composition need to be considered when evaluating plant-mediated effects on ecosystem nutrient cycling following eutrophication.…”
Section: Primary Productionmentioning
confidence: 99%